PEMANFAATAN PODCAST SEBAGAI MEDIA INFORMASI DAN EDUKASI PADA ERA TEKNOLOGI SAAT INI - Yarisda, Viona Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Advances in information and communication technology have changed the media landscape in the current digital era. Podcasts have become a popular media platform in recent years, podcasts can also provide a new way to convey information and education, this journal explains the use of podcasts as a medium for information and education in the technological era, as well as discussing the benefits, challenges and best strategies for producing and distributing content Podcast Effectively. This journal uses qualitative research methods in this journal using references to previous research. This research shows that podcasts have advantages as information and educational media. Podcasts have also proven effective in conveying an implicit message to listeners.Keywords: Podcast, Education, Information Media